Illegal Online Loans in Indonesia: Between the Law Enforcement and Protection of Victim - Angkasa Angkasa; Filep Wamafma; Ogiandhafiz Juanda; Bhanu Prakash Nunna (Universitas Negeri Semarang, 2023)
The phenomenon of online loans in Indonesia is becoming increasingly prevalent, accompanied by the proliferation of online loan provider services. However, this growth has also led to numerous instances of fraudulent practices within the online lending sector. This study aims to analyze the effectiveness of law enforcement and victim protection in cases of illegal online lending in Indonesia by comparing relevant laws and regulations. The findings of this study reveal that illegal online loans have severe consequences, resulting in victims suffering from material loss, psychological distress, physical harm, and social ramifications. Unfortunately, the current state of law enforcement falls short of delivering justice to the victims, as evidenced by the leniency of sentences imposed on offenders.